[OP.3A.03] IMPACT OF STRESS REACTION ON THE ASSESSMENT OF LATERALIZATION DURING SEQUENTIAL ADRENAL VEIN SAMPLING FOR PRIMARY ALDOSTERONISM. (September 2016) - Rossitto, G.; Seccia, T.M.; Battistel, M.; Barbiero, G.; Maiolino, G.; Bisogni, V.; Plebani, M.; Miotto, D.; Rossi, G.P.
Abstract : Objective: Emotional and pain-related stress occurring upon starting Adrenal Vein Sampling (AVS) has been shown to wane swiftly and to influence the selectivity of the procedure. It can also conceivably affect lateralization assessment when the sequential catheterization technique is used, which occurs in about half of cases at major referral centers. We set up this study to investigate the impact of stress reaction on accuracy of sequential AVS for the subtyping of Primary aldosteronism (PA). Design and method: We prospectively collected adrenal veins and VCI blood samples simultaneously at starting AVS (t-15) and after 15 min (t0) in 140 consecutive PA patients. In patients with selective AVS, a sequential technique was simulated by calculating the LI with plasma aldosterone (PAC) and cortisol (PCC) obtained at t-15 from one side and values at t0 from the contralateral side. These LI values (LIseq) were compared to those obtained with simultaneous sampling at t0 (LI_t0) using paired T and McNemar tests, and ROC curves analysis, for diagnostic accuracy, using a conclusive diagnosis of aldosterone-producing adenoma (APA) diagnosis (by the four corners criteria), as gold standard. Results: LI_t0 provided a significantly more accurate identification of APA compared to LI_seq, regardless of the sequential protocol simulated (AUC t0 = 0.869; "first right" AUC = 0.794 and "first left" AUC = 0.721; p = 0.029 and p = 0.002 for AUC comparison with t0, respectively). Figure. No caption available. Conclusions: In the subtyping of PA by AVS, when the sequential technique is used and the time delay between the first and the second adrenal vein sampling is about 15 minutes, a stress reaction lowers the accuracy of AVS for ascertaining lateralization of aldosterone excess, likely due to generation of artificial gradients between the sides.